Про граничні вирази лімітант Кояловича - Чехов, В.М.; Пан, А.В. (Видавничий дім "Академперіодика" НАН України, 2007)
A new theorem about limit expressions for the Koialovich's limitants is formulated and proved. These limit expressions allow us to estimate the solution of an infinite system without use of the successive approximations. Estimations of the solution are made for the problem of bending a thin rectangular clamped plate.